Jáchymov's Münzmeister Nicolas (Klaus) Kraus and his Activities in the Trade with Bohemian Silver between 1530-1535 (Theatrum historiae, 2006)
The author has found some new resources that specify the time of the work of Nicolas Kraus in the office of the Jáchymov´s Münzmeister. The article also describes the transition of this office from the administration of former private operators of the mint (the family of the Šliks of Pasoun) to the royal administration. The author came to the conclusion that the fundamental stage of this transition went ahead in 1532 when the office of the Jáchymov´s Münzmeister was subordinated to the office of the Oberst Berghauptmann Christoph Gendorf of Gendorf. In 1533 the law-suit started up when Kraus was accused by Gendorf from machination with precious metal. The Münzmeister answered with a countercharge and denounced Gendorf for corruption behaviour. The Oberst Berghauptmann – Kraus said – requested from him the amount of 300 guldens out of the ordinary account evidence every year. The law-suit was solved by the Kammergericht of the Bohemian kingdom and this court advanced this case to the king´s own resolution in 1535. Finally, the affair – originally there were also demanded capital punishments – was finished by money penalty. However the amount was recovered from the Jáchymov´s citizens because they took a financial guarantee for Nicolas Kraus in the times of his accession to the office of Münzmeister at the beginning of 1530.